BUDAYA PIMALI DALAM JUAL BELI PADA MASYARAKAT PATTAE - Syarif, Suryadi; Bedong, M. Ali Rusdi; Zaenong, A. M. Anwar (LPPM IAIN Parepare, 2019)
This research aims to describe pamali in trading of Pattae society. This study used descriptive qualitative method. Data was collected by observation, interview, and documentation. The findings showed that pamali culture in trading of Pattae society is a legacy from ancestors that descended from generation to generation. It is a belief that is never done and has become a habit of society. However, some people do not trust the tradition any more because they think it is not in accordance with this era and it also makes people difficult to carry out trading activities.